An Fe(III) complex with the dianionic form of 2,6-diacetylpyridine bis(acylhydrazone). The crystal structure of [diaqua-2′,2â´-(2,6-pyridinediyldiethylidyne)dioxamo-hydrazide] iron(III) perchlorate trihydrate, [Fe(dapsox)(H2O)2]ClO4· 3H2O - Andjelkovic, K.; Bacchi, Alessia; Pelizzi, Giancarlo; Jeremic, D.; Ivanovic-Burmazovic, Ivana (Journal of Coordination Chemistry, 2002)
The title compound was prepared by a template synthesis from 2,6-diacetylpyridine, dioxamohydrazide and Fe(ClO) · 6HO (mol ratio 1: 2: 1) in MeOH/HO (3: 1) solution and its structure determined by single-crystal X-ray diffraction; triclinic, space group P1, a = 7.5186(7), b = 10.9730(9), c = 14.6110(10)Å, α = 95.866(1), β = 100.252(1) γ = 92.895(1), z = 2. The polydentate ligand is coordinated as a dianionic pentadentate while water molecules occupy apical positions in the structure. This is the first example of a monomeric, pentagonal bipyramidal structure of an Fe(III) complex with a dianionic bis(acylhydrazone) derivative of 2,6-diacetylpyridine.